For such a time as this : my faith journey through the White House and beyond - McEnany, Kayleigh (Liberatio Protocol, 2021)
The former presidential press secretary chronicles her journey to the White House, offering never-before-told anecdotes about what really happened within the Trump administration, and how her faith got her through some of the most high stakes moments in the West Wing.